Acoustical adaptation of the Thessaloniki music-theatre - G. PAPANIKOLAOU (Archives of Acoustics)
Acoustical adaptation design for a musical theatre situated in a residential building at Thessaloniki downtown is described. Peculiar details of the completed adaptation are discussed and some conclusions derived, stressing the importance of a high sound insulation level as a factor of the good acoustical quality of concert halls.